Real-time observation of coherent spin wave handedness - Taewoo Ha; Kyung Ik Sim; Howon Lee; Hyun Jun Shin; Sanghoon Kim; Se Kwon Kim; Jae Hoon Kim; Dong-Soo Han; Young Jai Choi; Byung Cheol Park (npj Spintronics)
Abstract Magnonics, a crucial domain in information science and technology, utilizes spin waves in magnets as efficient information carriers. While antiferromagnets have been suggested for versatile magnonic platform because of the coexistence of right- and left-handed spin waves, their energetic degeneracy poses challenges for observation through spectral measurements, limiting their applicability. Recent observations of distinct spin wave handedness within the gigahertz regime have reported but, are yet to be demonstrated in terahertz (THz) frequencies of antiferromagnetic spin waves. Most of all, the coherence of spin waves is a key aspect of quantum information. Here, employing THz time-domain spectroscopy—a direct, precise, and easy probe for monitoring coherent spin wave dynamics—we discern chiral antiferromagnetic spin waves of opposite phase windings in the time domain, noting their handedness reversal across the angular momentum compensation temperature in ferrimagnets. We establish a principle for directly measuring the handedness of coherent antiferromagnetic spin waves in ferrimagnets with net magnetic moment M ≠ 0 but angular momentum L = 0. Our multidimensional access in the time and spectral domain enables the accurate determination of critical temperature and the dynamic observation of coherent chiral spin waves simultaneously in a single experiment, with potential applications in exploring other quantum chiral entities.